2017
DOI: 10.3390/molecules22071098
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Pyrenylated Coumarins from the Roots of Prangos hulusii

Abstract: The dichloromethane extract of the roots of Prangos hulusii, a recently described endemic species from Turkey, has yielded nine known and one new prenylated coumarins. The structures were elucidated by spectroscopic methods and direct comparison with the reference compounds where available. The root extract and its prenylated coumarins exhibit antimicrobial activity against nine standard and six clinically isolated strains at a concentration between 5 and 125 µg/mL. In particular, the new coumarin, 4′-senecioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 19 publications
2
40
0
2
Order By: Relevance
“…This compound is present in Angelica dahurica, Notopterygium incisum, Ferula lutea, Angelica pubescens, and Peucedanum praeruptorum. Isoimperatorin exhibits various pharmacological activities, including antioxidant [255,256], anti-inflammatory [257], analgesic [258], antibacterial [259,260], and anticancer properties [261,262]. Wijerathne et al reported that isoimperatorin protected against OA-induced asthma via mitigation of airway inflammation and mucus hypersecretion evidenced by the decreased IL-4, IL-5, and IL-13 production [257].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…This compound is present in Angelica dahurica, Notopterygium incisum, Ferula lutea, Angelica pubescens, and Peucedanum praeruptorum. Isoimperatorin exhibits various pharmacological activities, including antioxidant [255,256], anti-inflammatory [257], analgesic [258], antibacterial [259,260], and anticancer properties [261,262]. Wijerathne et al reported that isoimperatorin protected against OA-induced asthma via mitigation of airway inflammation and mucus hypersecretion evidenced by the decreased IL-4, IL-5, and IL-13 production [257].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…Bactericidal and fungicidal efficacy of the naturally occurring or synthetic coumarin derivatives are commonly investigated in literature (Hamdi et al, 2008;Siddiqui et al, 2011;Dastan et al, 2016;Singh et al, 2017;Tan et al, 2017). To date, the significant inhibitory activity of several biologically active coumarin-based compounds has been demonstrated on K. pneumoniae (Siddiqui et al, 2011; Tan et al, 2017). Based on the antibacterial potential of the coumarin derivatives, we suggest ZINC95543764, the top most energy scored compound in this study, as a potential Klebsiella inhibitor.…”
Section: Identification Of Potential Drugs For Kdsamentioning
confidence: 98%
“…This compound is a derivative of coumarin, and it is reported to have too low acute toxicity in mice, with high antimicrobial and antioxidant potential (Hamdi et al, 2008). Bactericidal and fungicidal efficacy of the naturally occurring or synthetic coumarin derivatives are commonly investigated in literature (Hamdi et al, 2008;Siddiqui et al, 2011;Dastan et al, 2016;Singh et al, 2017;Tan et al, 2017). To date, the significant inhibitory activity of several biologically active coumarin-based compounds has been demonstrated on K. pneumoniae (Siddiqui et al, 2011; Tan et al, 2017).…”
Section: Identification Of Potential Drugs For Kdsamentioning
confidence: 99%
“…Moreover, coumarins are considered as a privileged scaffold in the design of compounds with several biological targets. Coumarin derivatives displayed a wide range of pharmacological activities like anti-cancer [188], among others [189][190][191][192][193].…”
Section: Coumarin Derivativesmentioning
confidence: 99%